Egoism or Altruism? The Influence of Cause-Related Marketing on Customers’ Extra-Role Behavior - Hui, Zhang; Wenan, Hu (Frontiers in Psychology, 2022)
Based on attribution theory and regulatory focus theory, this paper discusses the influence mechanism of cause-related marketing on customers’ extra-role behavior and the moderating effect of customer promotion focus and prevention focus. The results show that egoistic cause-related marketing has a negative impact on customer extra-role behavior, while altruistic cause-related marketing has a positive impact on customer extra-role behavior. Customer promotion focus has a significant positive moderating effect on the negative impact of egoistic cause-related marketing on customer extra-role behavior; customer promotion focus also has a significant positive moderating effect on the positive effect of altruistic cause-related marketing on customer extra-role behavior. There is a significant negative moderating effect of customer prevention focus on the negative impact of egoistic cause-related marketing on customer extra-role behavior, while there is a significant positive moderating effect of customer prevention focus on the positive impact of altruistic cause-related marketing on customer extra-role behavior.